The Body and Senses in Martial Culture - Loh, H.L.L.; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This ethnographic study of a mixed martial arts gym in Thailand describes the everyday practices and lived experiences of martial art practitioners. Through the lived realities and everyday experiences of these fighters, this book seeks to examine why foreigners invest their time and money to train in martial arts in Thailand; the linkages between the embodiment of martial arts and masculinity; how foreign bodies consume martial arts and what they get out of it; the sensory reconfiguration required of a fighter; and the impact of transnational flows on bodily dispositions and knowledge. The author argues that being a successful fighter entails not only sensitized awareness and knowledge of one's body, but also a reconfiguration of the senses.
Chapter 1: Introduction -- Chapter 2: Methodology -- Chapter 3 -- The Lived Realities at the Gym -- Chapter 4: Knowing your Body -- Chapter 5: The Global Martial Circuit and Globalised Bodies -- Chapter 6: Conclusion.
Keywords: Human body-Social aspects; Sports-Sociological aspects